Strain engineering a multiferroic monodomain in thin-film BiFeO3 - Waterfield Price, N; Vibhakar, A; Johnson, R; Schad, J; Saenrang, W; Bombardi, A; Chmiel, F; Eom, C; Radaelli, P (American Physical Society, 2019)
The presence of domains in ferroic materials can negatively affect their macroscopic properties and hence their usefulness in device applications. From an experimental perspective, measuring materials comprising multiple domains can complicate the interpretation of material properties and their underlying mechanisms. In general, BiFeO3 films tend to grow with multiple magnetic domains and often contain multiple ferroelectric and ferroelastic domain variants. By growing (111)-oriented BiFeO3 films on an orthorhombic TbScO3 substrate, we are able to overcome this, and, by exploiting the magnetoelastic coupling between the magnetic and crystal structures, bias the growth of a given magnetic-, ferroelectric-, and structural-domain film. We further demonstrate the coupling of the magnetic structure to the ferroelectric polarisation by showing the magnetic polarity in this domain is inverted upon 180° ferroelectric switching.